2020
DOI: 10.1177/0021998320968137
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and physical investigation of an artificial stone produced with granite residue and epoxy resin

Abstract: The incorporation of ornamental stones residues to a polymer resin to produce artificial stone is an alternative to reducing the environmental impacts of inadequate waste disposal; it also represents a technically viable method. The objective of study was to develop an artificial granitic stone (AGS) using 85% in mass of granite agglutinated by 15% epoxy resin, through a vacuum, vibration and compression process. The artificial stone presented superior properties when compared with the natural granite, it had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…These values indicate that artificial stone is 448% more resistant to abrasion than natural stone, commercialised on a large scale. Another study involving artificial rocks, based on granitic rocks, found little variation in resistance, ranging from 1.13 mm (natural rock) to 1.46 mm (artificial rock), in a cycle of 1000 meters (GOMES et al, 2021), demonstrating a greater performance gain in the composite developed in this study. This gain in abrasion resistance occurs due to the presence of the resin that has greater mechanical strength.…”
Section: Characterisation Of Artificial and Commercial Slabsmentioning
confidence: 53%
See 1 more Smart Citation
“…These values indicate that artificial stone is 448% more resistant to abrasion than natural stone, commercialised on a large scale. Another study involving artificial rocks, based on granitic rocks, found little variation in resistance, ranging from 1.13 mm (natural rock) to 1.46 mm (artificial rock), in a cycle of 1000 meters (GOMES et al, 2021), demonstrating a greater performance gain in the composite developed in this study. This gain in abrasion resistance occurs due to the presence of the resin that has greater mechanical strength.…”
Section: Characterisation Of Artificial and Commercial Slabsmentioning
confidence: 53%
“…These stones can be formed by a high content of natural aggregates and a low content of polymeric binder in their composition, presenting good mechanical properties and low porosity, compared to natural stones (RIBEIRO, 2015). Da Cunha Demartini, Rodríguez and Silva (2018), Gomes et al (2021) and Shishegaran et al (2022) proved the technical feasibility of producing artificial stone from the agglutination of resin and rock wastes, showing that this stone can be a technically, economically and ecologically viable alternative.…”
Section: Introductionmentioning
confidence: 96%
“…The appropriate weight ratio of epoxy resin for preparing the epoxy granite composite with the selected granite granular size is determined according to the following equations to determine the minimum resin content (MRC%) [11].…”
Section: Samples Preparationmentioning
confidence: 99%
“…they found that epoxy granite composite with resin ratio between 60% to 70% is the most suitable composite for structural and engineering applications like machine tools structure. Maria Luiza et al [11] showed that epoxy granite composite had satisfactory physical and mechanical properties, like resistance to temperature oscillations, and high resistance to wear and impact. Selvakumar et al [12] carried out numerical, analytical, and experimental studies on specimens of steel, cast iron, and epoxy granite at constant stiffness to compare the properties of structures from these materials more precisely.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) images and density were conducted over the specimens fabricated. This research is a local strategy [26][27][28] for giving use to some of the hazardous wastes in Colombia, and therefore contribute with initiatives such as recycling, 29 green materials, 30,31 and circular economy 32 of materials and processes.…”
Section: Introductionmentioning
confidence: 99%